Assessment of health equity consideration in masking/PPE policies to contain COVID-19 using PROGRESS-plus framework: a systematic review - Anindit Chhibber; Aditi Kharat; Dylan Kneale; Vivian Welch; Mukdarut Bangpan; Nathorn Chaiyakunapruk (BMC Public Health, 2021)
Abstract Introduction There is increasing evidence that COVID-19 has unmasked the true magnitude of health inequity worldwide. Policies and guidance for containing the infection and reducing the COVID-19 related deaths have proven to be effective, however the extent to which health inequity factors were considered in these policies is rather unknown. The aim of this study is to measure the extent to which COVID-19 related policies reflect equity considerations by focusing on the global policy landscape around wearing masks and personal protection equipment (PPE). Methods A systematic search for published documents on COVID-19 and masks/PPE was conducted across six databases: PubMed, EMBASE, CINAHL, ERIC, ASSIA and Psycinfo. Reviews, policy documents, briefs related to COVID-19 and masks/PPE were included in the review. To assess the extent of incorporation of equity in the policy documents, a guidance framework known as ‘PROGRESS-Plus’: Place of residence, Race/ethnicity, Occupation, Gender/sex, Religion, Education, Socioeconomic status, Social capital, Plus (age, disability etc.) was utilized. Results This review included 212 policy documents. Out of 212 policy documents, 190 policy documents (89.62%) included at least one PROGRESS-plus component. Most of the policy documents (n = 163, 85.79%) focused on “occupation” component of the PROGRESS-plus followed by personal characteristics associated with discrimination (n = 4;2.11%), place of residence (n = 2;1.05%) and education (n = 1;0.53%). Subgroup analysis revealed that most of the policy documents (n = 176, 83.01%) were focused on “workers” such as healthcare workers, mortuary workers, school workers, transportation workers, essential workers etc. Of the remaining policy documents, most were targeted towards whole population (n = 30; 14.15%). Contrary to “worker focused” policy documents, most of the ‘whole population focused’ policy documents didn’t have a PROGRESS-plus equity component rendering them equity limiting for the society. Conclusion Our review highlights even if policies considered health inequity during the design/implementation, this consideration was often one dimensional in nature. In addition, population wide policies should be carefully designed and implemented after identifying relevant equity related barriers in order to produce better outcomes for the whole society.